2018
DOI: 10.5327/z2176-947820180345
|View full text |Cite
|
Sign up to set email alerts
|

Cálculo de risco e detecção de queimadas: uma análise na Amazônia Oriental

Abstract: O sensoriamento remoto e o índice de risco de fogo são as formas de detecção e previsão de queimadas utilizadas pelo Instituto Nacional de Pesquisas Espaciais para monitorar a frequência de queimadas no Brasil, no entanto observa-se que a ocorrência de uma queimada nem sempre é prevista pelo índice do risco de fogo, particularmente na região da Amazônia oriental. Assim, esta pesquisa foi motivada pelo objetivo de analisar o padrão espaçotemporal das queimadas detectadas via satélite e a eficiência dos alertas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(25 reference statements)
1
7
0
1
Order By: Relevance
“…Even though there are no indications of any direct relationship between intense drought events and fire occurrence in the central portion of Brazil (Cunha et al, 2019), the burnt area and the hotspot peaks in 2010, as well as those in 2015 and 2017, coincided with extreme drought events that occurred in the region (Ribeiro et al, 2018;Cunha et al, 2019). For example, in the Eastern Amazon Sodré et al (2018) identified some relationship between less rainy periods and an increase in hotspots, and most of the hotspots were in anthropized areas. Projections indicate that with increasing temperatures as a result of climate change, fire events in the Cerrado may increase later this century (Silva et al, 2019).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Even though there are no indications of any direct relationship between intense drought events and fire occurrence in the central portion of Brazil (Cunha et al, 2019), the burnt area and the hotspot peaks in 2010, as well as those in 2015 and 2017, coincided with extreme drought events that occurred in the region (Ribeiro et al, 2018;Cunha et al, 2019). For example, in the Eastern Amazon Sodré et al (2018) identified some relationship between less rainy periods and an increase in hotspots, and most of the hotspots were in anthropized areas. Projections indicate that with increasing temperatures as a result of climate change, fire events in the Cerrado may increase later this century (Silva et al, 2019).…”
Section: Resultsmentioning
confidence: 97%
“…Grass areas, such as pastures, are more conducive to burning since they have less combustible material and more higher-combustion material. On the other hand, agricultural areas have more biomass and higher humidity and consequently need more time to reach burning-conducive conditions (Sodré et al, 2018).…”
Section: Fire Regime In Goiás -Brazil and Mozambique Between 2010 And...mentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques used to discourage the practice of using fire among traditional rural producers have only recently succeeded and the frequency of fires in the country continues to be high. Sodré et al (2018) point out that the reluctance to reveal occurrences is caused by economic factors, associated with cheap and rapid actions to create clean and fertilized soil.…”
Section: Characterization Of the Factors That Involve Fire Issues In The Western Amazonmentioning
confidence: 99%
“…Another worrying and little-known fact are how climate change and the indiscriminate use of fire to clean and eliminate trees, grass, and weeds can contribute to changes in the hydrological cycle. This concern worsens even more during the occurrence of the La Niña phenomenon, when the risk of fire is increased (SODRÉ et al, 2018). The first mathematical models presented as a forest tipping point a deforestation rate of 40%.…”
Section: The Amazon and The Climate Changementioning
confidence: 99%